Estudo da inclusão de compartimentos em biodigestores modelo canadense - Oliveira, Matias Marchesan de (2012)
The piggery for many years was characterized as a waste-generating activity of high polluter, but in recent decades many studies are responsible for changing this concept. The use of biodigester is well disseminated to lessen the impacts generated by this activity, gaining encouragement deployment in recent years, by encouraging the use of renewable energy. The biodigester is responsible for the production of biogas used as alternative energy on farms that have the digesters system. We observed few studies that investigate the geometry of the digesters and its effects on anaerobic digestion process. This work aimed to study the partitioning of the Canadian model digester anaerobic digestion of swine waste applied to evaluating the degradation (removal) of the physic-chemical parameters (temperature, pH, COD, BOD5, total nitrogen, total phosphorus, total solids, total fixed solids and total volatile solids), and determining a kinetic model describing the biogas produced in each of the compartments of the digesters. For the study were built three reactors in bench scale: the first with a partitioning which caused variation of the horizontal flow, the second with partitioning which flux change generated in the vertical and third, without fragmentation, to be used as a reactor testimony. The analyzes of the physicchemical parameters were made according to Standard Methods for the Examination of Water and Wastewater, since the determination of the kinetic model was done considering the existence of a plug flow (tubular reactor) to each of the reactors constructed and to qualification of biogas was use a gas chromatograph. On the analysis of physic-chemical was second reactor (flow variation vertically) that showed that showed a significant difference in the efficiency of COD removal and pH values, and this reactor also showed better removal of solids and BOD5. Already temperature, showed similar behavior in the three reactors, characterizing the anaerobic digestion occurred primarily in the mesophilic range. Considering the BOD5 as a substrate was obtained as rate constant 0.021 d-1, 0.025 d-1 and 0.024 d-1, respectively for the first, second and third reactor. However, considering the COD as a substrate was obtained 0.032 d-1, and 0.034 d-1, 0.027 d-1 for each of the reactors. Kinetic models had a higher correlation with the experimental data when considering the COD as substrate, and was the second reactor with the highest correlation (R2 = 0.599). In the evaluation of biogas the three reactors not showed difference between them.